THE EFFECT OF USING THE CHAIN WRITING METHOD IN TEACHING WRITING OF ANALYTICAL EXPOSITION TEXT TO INDONESIAN EFL LEANERS - Mayasari, Eka; Masruroh, Siti Na’imatul (GoAcademica CRP, 2024)
The purpose of this research was to determine the effectiveness of using the chain writing method on students' writing skills on analytical exposition texts in eleventh grade students of SMAIT As-Sakinah. The problem in this research is the students' difficulties in writing English texts. The formulation of the problem in this research is to determine the extent to which the use of the chain writing method influences students' writing of analytical exposition texts. This research is a quasi- experimental study using two classes; experimental class (XI Al-Qolam), taught using the chain writing method and control class (XI Az-Zuhruf), taught without using the chain writing method. 34 students make up the population, whereas 17 students make up the sample. Pre-test and post-test tests were two different sorts of tests used in data collection techniques. The data collected for this investigation were analyzed using the t-test, various tests to assess the degree of relevance of the research's findings. The experimental class's pre-test results revealed that the students' aptitude for writing analytical exposition text was low. 49.94 were the typical pre-test score. The average post-test score was 78.82 after treatment, and the t-test table had a magnitude of Ha: 0.000, indicating that chain writing is successful in instructing students to write analytical exposition texts. According to the research's findings, students at SMAIT As-Sakinah Sebauk in Tanjungpinang's eleventh grade are much less able to compose analytical exposition texts when they employ the chain writing method.